Potensi Pengembangan Wellness Tourism sebagai Salah Satu Daya Tarik di Heavenly Spa di Hotel The Westin Resort & Spa Ubud, Bali - Julisman, Stephanie Natalie; Tirtadidjaja, Andari (Universitas Batanghari Jambi, 2024)
Wellness tourism is a tourism that is currently in demand by tourists and has become a new attraction in society, especially in the Ubud area, Bali. Heavenly spa is a place that uses the concept of wellness tourism as an attraction for tourists. This study aims to determine the development of wellness tourism as an attraction at Heavenly Spa. This study uses a descriptive method with a qualitative approach. Data collection techniques are observations conducted at Heavenly spa, in-depth interviews with Heavenly spa managers and visitors, documentation such as photos and documents needed to support data completeness. The results of this study are that Heavenly spa has an attraction such as beautiful natural scenery, and offers various wellness and spa activities that can be followed by hotel guests. Access to the Westin hotel from the airport can be said to be easy because there is a lot of transportation provided such as buses, online motorcycle taxis, and the hotel also provides a shuttle service from the airport. The facilities provided by the Westin hotel are very helpful for this wellness activity because the hotel provides different places according to hotel activities such as for yoga, the hotel provides 2 places, namely the yoga pavilion and the yoga terrace with a different atmosphere. The impact generated by this wellness activity is in terms of economy, there is an increase in visits to Heavenly Spa.